LIBERICA COFFEE FARMERS GROUP COMMUNICATION PATTERN FOR SUPPORT OF SUKOREJO ECOTOURISM - Prima Mulyasari Agustini; Eli J. Miharja; Tuti Widiastuti (Universitas Prof. Dr. Moestopo (Beragama), 2020)
Tanjung Jabung Barat which is a peatland with the main commodity production of Liberica Coffee, the area is being developed by oil and gas companies and governments into ecotourism destinations. Ecotourism development is considered to be able to improve the walfare of the community and also maintain the conservation value of the coffee ecosystem. Liberica Coffee farmers are empowered to support ecotourism. This paper aims to describe about: (1) Interaction between Liberica Coofee farmers and their interactions with the stakeholders, (2) A one-way and two-way communication hierarchy between farmers and the stakeholders, and (3) the mapping of communication networks between liberica coffee farmers and the stakeholders. This study was conducted using qualitative methods with interviews and FGD were conducted with Liberica Coffee farmers, the company and the local government. The conclusion of this paper indicate that: (1) coffee farmers carry out intensive and long duration communication conducted at the coffee beans processing site. (2). Communication generally takes two directions so there is a tendency for farmers to take action and move together without waiting for orders, and (3) Communication is carried out by the leader of the farmer group with the stakeholders also carrried out intensively and patterned so that it can support the development of the ecotourism in Sukorejo Liberica Coffee Village in a realtively short period of time.